2012
DOI: 10.1007/978-1-4614-1228-1
|View full text |Cite
|
Sign up to set email alerts
|

Glasses and Glass Ceramics for Medical Applications

Abstract: ), except for brief excerpts in connection with reviews or scholarly analysis. Use in connection with any form of information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed is forbidden. The use in this publication of trade names, trademarks, service marks, and similar terms, even if they are not identifi ed as such, is not to be taken as an expression of opinion as to whether or not they are subject to proprietary right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 0 publications
4
70
0
4
Order By: Relevance
“…It has been reported that the probable cause of porcelain chipping leading to delamination is due to the stress generated by CTE mismatch between the zirconia substructure and veneering porcelain 16,17) . In the case of lithium disilicate, CTE mismatch would be less of a consequence since it has a low CTE 12) , which is also compatible with both feldspathic porcelain and zirconia. Therefore, the CTE of lithium disilicate glass-ceramic liner tends to be stable after multiple firings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the probable cause of porcelain chipping leading to delamination is due to the stress generated by CTE mismatch between the zirconia substructure and veneering porcelain 16,17) . In the case of lithium disilicate, CTE mismatch would be less of a consequence since it has a low CTE 12) , which is also compatible with both feldspathic porcelain and zirconia. Therefore, the CTE of lithium disilicate glass-ceramic liner tends to be stable after multiple firings.…”
Section: Discussionmentioning
confidence: 99%
“…is another type of glass ceramic which offers thermal shock resistance, thus leading to a more stable CTE after multiple firing 12) . Moreover, lithium disilicate has CTE close to that of the veneering feldspathic porcelain and zirconia substructure.…”
Section: Introductionmentioning
confidence: 99%
“…Probably, rankinite could form amorphous or glass-ceramic structures able to blind barium and prevent its releasing. 23,24,25) This behaviour seems to be related to its low melting point, of about 1 450°C (Fig. 7), and to the presence of other oxide which can alter the tetrahedral chains order.…”
Section: Low Feo Slag (C1 To C3)mentioning
confidence: 98%
“…Mika fazının oluşumu ile ilgili en önemli reaksiyon potasyum feldspat ile MgF2 arasındaki etkileşim olarak rapor belirtilmiştir. Bu fazın kristallenmesi ile ilgili bir diğer yaklaşımda; uygun bileşenlerin olduğu bir ortamda 1000 o C sıcaklıklarda forsterite ve MgF2 'nin etkileşimi ile meydana gelen reaksiyondur [13]. Bu çalışmada meydana gelen Mika fazının ikinci yaklaşıma uygun şekilde oluştuğu düşünülmektedir.…”
Section: Deneysel çAlişmalar (Experimental Procedure)unclassified
“…Genel olarak mika kristalleri iki tetrahedral tabaka arasındaki bir oktahedral tabaka olarak yapılanır. Oktahedral tabaka oksijen, hidroksil ve katyonların bulunduğu florin gruplarını içerirken, tetrahedral tabakalar ise hegzagonal ağda birbirine bağlı Si-O tetrahedronlarından oluşur [13]. Mika kristalleri bu şekilde tekrarlı olarak üç boyutlu bünyede tabakalı yapıda uzanırlar.…”
Section: Deneysel çAlişmalar (Experimental Procedure)unclassified